APLIKASI STOCK OPNAME OBAT BERBASIS ANDROID DI FARMASI KLINIK JALUR FARMA KOTA SUKABUMI - Heru Hoerudin (Jurnal Teknologi Informatika dan Rekayasa Terapan, 2026)
Drug inventory management is an important aspect of pharmacy operations that requires high accuracy and precision. At Jalur Farma Clinic Pharmacy, Sukabumi City, stock opname activities are still conducted manually using stock cards, Microsoft Excel, and Word, causing recording errors, delayed reporting, and stock discrepancies. This study aims to design and develop an Android-based drug stock opname application to improve inventory management efficiency. The system development method used is Waterfall, consisting of requirement analysis, system design, implementation, testing, and maintenance. The application was developed using Android Studio with Kotlin programming language, PHP backend, and MySQL database. Main features include dashboard, medicine data management, stock in/out transactions, barcode-based stock opname, discrepancy audit, and PDF/Excel report export. The results indicate that the application improves stock opname speed, reduces recording errors, and generates real-time reports automatically. This system is expected to enhance operational efficiency at Jalur Farma Clinic Pharmacy.